Saliva as a Diagnostic Tool in Oral Diseases - (:unkn) unknown (My University, 2020)
Saliva is a body fluid, which is secreted from 3 major salivary glands (parotid, submandibular and sublingual) and many minor salivary glands. It contains organic and inorganic substances with 99% water, and has several functions such as contribution to articulation, digestion, cleansing and protection of the oral mucosa, and antimicrobial effects. The concentration of saliva’s substances vary according to the responses to physiological processes in the human body. Containing genetic materials such as DNA and RNA also highlights saliva as a potential diagnostic tool. Saliva analysis has advantages such as being cheaper, non-invasive, easier patient cooperation, and low technical sensitivity compared to blood tests; it can be used in the diagnosis of many diseases or routine risk assessments. It is also promising for its advantages in collection and storage of the samples. Advances in molecular biology, genomics, and proteomics have revealed the importance of saliva in the detection of many diseases, coining the term salivaomics. The early diagnosis of the diseases in which symptoms can be seen in late stages, may provide an easier treatment and improve the prognosis. In this review, the biomarkers of saliva in the presence of different diseases and the advantages of their use in diagnosis were examined.

Tükürük; başlıca üç majör tükürük bezi (parotid, submandibular _x000D_ ve sublingual) ve birçok minör tükürük bezinden salgılanan bir _x000D_ vücut sıvısıdır. İçerisinde %99 suyla birlikte organik ve inorganik _x000D_ maddeler bulunduran tükürüğün; artikülasyon, sindirim, ağız mu?kozasının temizlenmesi ve korunması ile antimikrobiyal etkiler gibi _x000D_ birçok işlevi vardır. Tükürüğün içerisindeki maddelerin konsantras?yonları vücuttaki fizyolojik süreçlere verilen yanıtlara göre değişik?lik gösterir. DNA ve RNA gibi genetik materyalleri barındırması da _x000D_ tükürüğü potansiyel bir teşhis aracı olarak öne çıkarmaktadır. Kan _x000D_ tahlillerine göre hasta kooperasyonunun daha kolay olması, daha _x000D_ ucuz, non-invaziv ve teknik hassasiyetin az olması gibi avantajları _x000D_ olan tükürük testleri; birçok hastalığın teşhisinde kullanılabileceği _x000D_ gibi rutin risk değerlendirmelerinde de kullanılabilir. Örnek toplan?ması ve saklanmasındaki avantajlarından dolayı da gelecek vaad _x000D_ etmektedir. Moleküler biyoloji, genomik ve proteomik alanlarında?ki gelişmeler sayesinde salivaomik terimi ortaya çıkmış ve birçok _x000D_ hastalığın saptanmasında tükürüğün önemi belirtilmiştir. Özellikle _x000D_ semptomların geç görülmeye başladığı hastalıkların tükürük test?leri sayesinde erken teşhis edilmesi, tedaviyi büyük oranda kolay?laştırabilir ve prognozu iyileştirebilir. Bu derlemede, farklı hasta?lıkların varlığında tükürükte bulunan biyobelirteçler ve teşhiste _x000D_ kullanımının avantajları incelenmiştir.
Ağız Hastalıklarında Tanı Aracı Olarak Tükürük